Interaction in open distance learning: Research issues in Malaysia - Dzakiria, Hisham (Penerbit Universiti Sains Malaysia, 2005)
Open Distance Learning (ODL) is an excellent method of reaching adult learners.It is truly a medium that helps to democratise education to all. Certainly in Malaysia, with the mushrooming of many dual mode institutions that offer ODL and the establishment of the Open University Malaysia (OUM) and other private institutions that offer ODL courses, education is being made accessible to all.For many Malaysians, pursuing ODL is just a matter of choice.With the competing priorities of work, home and school, adult learners desire a high degree of flexibility.The structure of ODL provides learners with the greatest possible control over the time, place and pace of education; however, learning at a distance is not without problems. Loss of student motivation due to the lack of face-to-face contact with teachers and peers, potentially high start up costs and lack of faculty support are all barriers to successful ODL.One particular important instructional element of contemporary ODL is interaction.It is a widely held belief that a high level of interaction is desirable and positively affects the effectiveness of any ODL course. However, it is not clear from research or evaluation data if interaction does improve the quality of learning in most ODL programmes.Furthermore, based on literature review, it is evident that little attention has been paid to the cost/benefits of interaction in terms of preparation time versus instructional effects.This article examines the research issues of interactivity in ODL in Malaysia.